Searching for Kaprekar's constants: algorithms and results - Byron L. Walden (International Journal of Mathematics and Mathematical Sciences)
We examine some new results on Kaprekar's constants, specifically establishing the unique 7-digit (in base 4) and 9-digit (in base 5) Kaprekar's constants and showing that there are no 15-, 21-, 27-, or 33-digit Kaprekar's constants.